2023
DOI: 10.1038/s41467-023-37703-6
|View full text |Cite
|
Sign up to set email alerts
|

FOXI3 pathogenic variants cause one form of craniofacial microsomia

Abstract: Craniofacial microsomia (CFM; also known as Goldenhar syndrome), is a craniofacial developmental disorder of variable expressivity and severity with a recognizable set of abnormalities. These birth defects are associated with structures derived from the first and second pharyngeal arches, can occur unilaterally and include ear dysplasia, microtia, preauricular tags and pits, facial asymmetry and other malformations. The inheritance pattern is controversial, and the molecular etiology of this syndrome is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Several copy number variations and signal nucleotide variations of genes were reported to be associated with craniofacial dysmorphism (Guida, Sparascio, et al., 2021 ; Zamariolli et al., 2019 ). In addition, several animal model studies have shown craniofacial dysmorphism in Foxi3 −/− mice (Mao et al., 2023 ; Singh et al., 2018 ; Youssoufian et al., 1986 ). In the study, we also found craniofacial dysmorphism in Foxi3 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several copy number variations and signal nucleotide variations of genes were reported to be associated with craniofacial dysmorphism (Guida, Sparascio, et al., 2021 ; Zamariolli et al., 2019 ). In addition, several animal model studies have shown craniofacial dysmorphism in Foxi3 −/− mice (Mao et al., 2023 ; Singh et al., 2018 ; Youssoufian et al., 1986 ). In the study, we also found craniofacial dysmorphism in Foxi3 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Qin et al (2021) found that loss-of-function variants in FOXI3 were found in patients with microtia and mandibular hypoplasia. Mao et al, 2023 identified 18 likely pathogenic variants of FOXI3 in 21 patients (3.1%) with craniofacial dysmorphism. Several animal model studies have shown abnormalities in the inner ear, jaw, outer and middle ears, heart and artery development, and thymus in Foxi3 −/− animals (Mao et al, 2023;Singh et al, 2018;Youssoufian et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our screening for causal mutations began with linkage analysis to pinpoint the suspected genomic locus for bilateral isolated constricted ear. We adhered to the quality control (QC) procedures outlined by Mao et al for pruning SNPs in strong linkage disequilibrium, removing SNPs with Mendelian errors, and verifying sex specifications 15 . Parametric multi-point linkage analysis was conducted on Pedigrees 1, 3, and 7, both individually and collectively, using MERLIN v.1.1.2 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Elucidating the function of cis-regulatory elements in specific cellular and temporal settings is key to unraveling the complex mechanisms of ear development and regulatory variations that influence the external ear phenotype 12,13 . Recent research underscores CNCCs as vital in craniofacial development, including the outer ear [14][15][16] . CNCCs positional identity is determined by a complex set of signaling factors that govern a distinct hierarchy of gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%